Derajat Infestasi dan Intensitas Ichthyophthirius multifiliis pada Ikan Koi (Cyprinus carpio) dengan Metode Kohabitasi [Degrees Infestation and Intensity Ichthyophthirius multifiliis On Koi (Cyprinus carpio) With Cohabitation Method] - Gunanti Mahasri; Dieswinta Hardika Aris; Rahayu Kusdarwati (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Marine and fisheries sector is one of the mainstay in the development of fisheries resources in Indonesia. Based on the fishery habitat fishery is divided into sea water, brackish water and freshwater. One result of freshwater fisheries potential that koi (C. carpio). Many of the obstacles that often harm the koi fish farming in producing a quality product. One of the obstacles which have a negative impact is a disease of fish. One type of disease most often a constraint due to the temperature of water in the koi fish is Ichthyophthiriasis. Parasiter disease in fish is caused by ectoparasites attack I. multifiliis. Artificial mode of transmission can be done to transmit I. multifiliis is by cohabitation which is an effort to pass the sick fish to healthy fish in a spot of maintenance. The existence of infestation I. multifiliis of fish will show clinical symptoms, degree of infestation and different intensity. This study aims to determine the degree of infestation and intensity I.multifiliis in fish koi (C. carpio) by the cohabitation method. The research method used was experiments method in the field carried out for cohabitation. Experimental method is a way to find a causal relationship (clause relations) between the two factors are intentionally inflicted by the researchers to eliminate or reduce and set aside other factors that could interfere (Arikunto, 2002). The results of this study indicate that the degree of infestation I.multifiliis on koi (C. carpio) during cohabitation indicate a mild degree of infestation, the degree of infestation and degree of infestation is heavy because the fish have different chances of infestation. Intensity I. multifiliis from day to day during the study experienced an increase ranging from 5,3 to 8,5 fish parasites every fish parasites.